DILEMA YURIDIS KLAUSULA EKSONERASI: ANTARA KEPASTIAN HUKUM PENGELOLA PARKIR DAN KEADILAN BAGI KONSUMEN - Hikmawati; Hasdar (Astha Grafika, 2025)
This study aims to analyze the legal validity of exoneration clauses in parking tickets that transfer liability for loss to consumers, and to reconstruct the legal relationship between operators and service users. The research method employed is normative juridical with a statutory approach and case analysis of Supreme Court jurisprudence. The results indicate that the legal relationship in modern parking is qualified as a custody agreement (bewaring), not land lease, implying a mandatory duty of care. It was found that the standard clause stating